Various Synthetic Pathways for the Synthesis of 3,4-Disubstituted Isoxazole by One Pot Multicomponent Reaction - Parul Setia; Ruchi Bharti; Renu Sharma (Orbital: The Electronic Journal of Chemistry, 2020)
Isoxazole is a five membered heterocyclic compound which is an azole with an oxygen atom next to nitrogen. The substituted isoxazole derivatives show various biological activities like antimicrobial, antiviral, anti-inflammatory, antioxidant, anticancer etc.  Isoxazoles are found in some natural products and also in number of drugs. Especially 3– methyl–4-arylmethylene substituted isooxazole is used as a main constituent in synthetic organic chemistry. Various approaches have been made for diverse synthesis of 3,4-distituted isoxazoles via multicomponent reaction using different catalyst. Each catalyst has its own effect on the synthetic rate, yield and reaction time of reaction. In this mini review we have reported the various catalytic effect on the single pot multicomponent synthesis of 3,4-disubstituted isoxazolones.DOI: http://dx.doi.org/10.17807/orbital.v12i4.1549